غزل گائیکی کا تعارف:آغاز و ارتقا - Yasir Iqbal (Tabeer e Nau, 2025)
Urdu ghazal and its singing are two different subjects. Much has been written on the art of Urdu ghazal, but the art of its singing has been made a rare subject. Ghazal singing is a separate and complete art. Its technical principles were in view of the ghazal writers. Music is very prevalent in Indian culture. Thus, the art of ghazal became a powerful plant in this civilization. This article discusses the beginning and evolution of the art of ghazal singing. Different periods and different styles of Ghazals singing are discussed. Modern styles of ghazal have been analysised in Lucknow and modern times.